AGROINDUSTRI PENGOLAHAN TANAMAN PANGAN DI KECAMATAN PONJONG KABUPATEN GUNUNG KIDUL - Ken Suratinah; Pinjung Nawang Sari; Nurina Sofiana; Radita Dwi Rahmi; Yogi Pradeksa (Universitas Sebelas Maret, 2014)
This research was purposed to know: 1) the properness of agroindustries utilize local crops as raw materials, 2) The added value and profit of agroindustry utilize the local crops as raw materials, 3) The poverty and prosperity level of farmer’s households in the research area. The kind of crops that researched are paddy, corn, soya beans, ground nuts, and cassava. This research located in two villages, Bedoyo village and Sumbergiri village, Kecamatan Ponjong, Kabupaten Gunung Kidul, Regency of Yogyakarta. The used basic method was analytic descriptive, with purposive approach to choose samples of the 90 farmer households which have crops fields and agroindustries. From the data analysis we can inform that: 1) Agroindustry using cassava, corn, soya beans, and ground nuts as raw materials were profitable and could absorb a lot of labors around the environtment with range of /C ratio betw een 1,13 – 186,17%, 2) Agroindustry using paddy as raw material was not profitable and ineffecient because its taking too much labor, 3) Average incomes of farmers about Rp 10.502.202/year and they are not in poverty, 4) Food agroindustries contribute to farmer’s income about Rp 14.021.262/year. It draws a conclussion food agroindustries have lots of adventages 1) help increasing farmer’s income 2) absorb labor from the environtment, 3) with grow the industries scale can increasing farmer’s skills and prosperity. Penelitian ini bertujuanuntuk mengetahui: 1) kelayakan, 2) nilai tambahdankeuntungan, 3) kemiskinandan kesejahteraanrumah tanggapetaniagroindustripengolahtanamanlokalsebagai bahan baku.Jenistanamanyangditelitiadalahpadi, jagung, kedelai,kacang tanah, danketela pohon. Penelitian dilakukan diDesaBedoyodanSumbergiri,KecamatanPonjong, Gunungkidul. Menggunakan metodedasaranalitikdeskriptif,dengan purposivesampling 90rumah tangga petaniyangmengusahakan tanamanpangandan agroindustrinya. Hasil analisis menunjukkanbahwa: 1) agroindustriberbahan baku ketela pohon, jagung, kedelai, dan kacang tanah menguntungkan danmampu menyerap banyak tenaga kerja (/Cantara1,13-186,17%), 2) agroindustriberbahan baku padi tidak menguntungkan dan tidak efisien karena mengambil terlalubanyak tenaga kerja, 3) pendapatan rata-rata rumah tangga tani Rp10.502.202/tahundan tergolong tidak miskin, 4) agro industri pangan berkontribusi terhadap pendapatanrumah tangga rata-rata sebesar Rp14.021.262/tahun. Kesimpulannya, agroindustripangan memiliki banyak keuntungan, yaitu: 1) meningkatkan pendapatan 2) menyeraptenaga kerja, 3) meningkatkan kesejahteraan petani.